2006
DOI: 10.1126/science.1134830
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis-Mediated Release of a Small RNA Inhibitor of RNA Polymerase

Abstract: Noncoding small RNAs regulate gene expression in all organisms, in some cases through direct association with RNA polymerase (RNAP). Here we report that the mechanism of 6S RNA inhibition of transcription is through specific, stable interactions with the active site of Escherichia coli RNAP that exclude promoter DNA binding. In fact, the DNA-dependent RNAP uses bound 6S RNA as a template for RNA synthesis, producing 14-to 20-nucleotide RNA products (pRNA). These results demonstrate that 6S RNA is functionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
258
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(271 citation statements)
references
References 25 publications
12
258
0
Order By: Relevance
“…Such a network of contacts was not present during the assembly of the artificial elongation complexes (18). Interestingly, Escherichia coli 6S RNA has been shown to block bacterial RNA polymerase from binding promoter DNA (19). Here, we found that binding of an inhibitory ncRNA to Pol II also prevented interaction with promoter DNA; however, in the eukaryotic system the interactions between Pol II and the GTFs allowed complexes that contained promoter DNA to form.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Such a network of contacts was not present during the assembly of the artificial elongation complexes (18). Interestingly, Escherichia coli 6S RNA has been shown to block bacterial RNA polymerase from binding promoter DNA (19). Here, we found that binding of an inhibitory ncRNA to Pol II also prevented interaction with promoter DNA; however, in the eukaryotic system the interactions between Pol II and the GTFs allowed complexes that contained promoter DNA to form.…”
Section: Discussionmentioning
confidence: 62%
“…Here, we found that binding of an inhibitory ncRNA to Pol II also prevented interaction with promoter DNA; however, in the eukaryotic system the interactions between Pol II and the GTFs allowed complexes that contained promoter DNA to form. The single-stranded region of 6S RNA can engage the active site of bacterial RNA polymerase and serve as a template for synthesis of short RNA transcripts, which functions to derepress transcription (19). Future studies will likely reveal whether an analogous regulatory mechanism can occur with B2 and Alu RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The nTSS for the RNase P RNA (rnpB), 4.5S RNA (ffs), 6S RNA, and tmRNA (ssrA) matched the published experimental data (15,16) or genome annotation. We also detected the very short 6S RNA-associated product RNA (pRNA) (17) starting at position c1686546, which corresponds to the bulge-internal adenosine position of Escherichia coli 6S RNA (17). Although the cyanobacterial pRNAs are slightly longer (19-30 nt) than their counterparts in E. coli (14-20 nt), their detection in a phylogenetically distant cyanobacterium suggests that 6S RNA-mediated regulation of RNA polymerase activity is very widely conserved.…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, though VirP1 appears to be important for PSTVd infection, there is no evidence for its involvement in replication (Kalantidis et al, 2007); instead, hypotheses center around its possible involvement in systemic spread of PSTVd (Maniataki et al, 2003) or in RNA-mediated DNA methylation (Kalantidis et al, 2007). d 70 , the "housekeeping" sigma factor involved in the transcription of most genes in growing bacterial cells (Gruber and Gross, 2003), is necessary for 6S RNA template transcription in E. coli (Wassarman and Saecker, 2006). Thus, this protein aids transcription of both DNA and RNA templates by a DdRP, though the mechanism by which it accomplishes a switch in substrate specificity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In response to nutrient availability, the DdRP transcribes a short RNA from the 6S RNA template that leads to desequestration of DdRP. This step in turn enables binding to DNA promoters and synthesis of protein-coding mRNAs (Wassarman and Saecker, 2006). Mammalian Pol II can bind to a hairpin formed by the noncoding B2 RNA and use the longer strand of the hairpin sequence as a template to extend the short strand by transcription.…”
Section: Introductionmentioning
confidence: 99%